DSP-based sinusoidal PWM signal generation algorithm for three phase inverters - Lesan, A.Y.E.; Doumbia, M.L.; Sicard, P. (2009 IEEE Electrical Power and Energy Conference, 2009)
Generation of DSP-based patterns to control voltage source inverters substantially helped the development of modern electric drives used in various applications. Although the DSP control is well known, there are few papers that cover in detail the control signal generation methodology. This paper presents a DSP-based algorithm to generate sinusoidal PWM signals. The sinusoidal PWM generation algorithm is written in C language so it can be reused easily, in addition to the flexibility it provides in terms of changing the PWM switching frequency and the fundamental frequency of the inverter output voltage. The algorithm development methodology and the experimental results are presented. The output voltage and current harmonic spectra are compared for 5 kHz and 10 kHz carrier frequencies. The results show the effectiveness of the proposed algorithm. This work is part of a research project that aims to develop sensorless vector control of induction machines. This part is presented separately to document DSP based PWM algorithm development process.